Overexpression Of Mirna-975 Induced Immune Genes And Abnormal Spermatogenesis In Drosophila Melanogaster - Manickam, Sharvin (2024)
Homeostasis is the measure of an organism’s evolutionary adaptation. Any oddities to the organism’s phenotype signal a system at disarray, with the full force of immune systems in response. When mir-975 was overexpressed, the apical tip of the d. Melanogaster’s testis was bulged, mirroring a tumour-like appearance, suggesting its homeostasis were ‘knocked off’ balance. Thence, the associations between mir-975, spermatogenesis and its innate immunity is to be investigated in this manuscript. To understand the bulged phenotype of the testis’s apical tip, the developmental stages of spermatogenesis had to be characterised, from the onset till late spermatocyte stage, whilst mir-975’s transcriptomics identifies which of the immune genes were in response to the said imbalanced homeostasis. To characterise the spermatogenesis of the bulged testis, antibodies complimentary to the aforesaid stages, matched to its appropriate markers each were incubated with dissected testes from control (actin5c-gal4 > oregon r) and transgenic progenies (actin5c-gal4 > uas-mir-975) respectively, using confocal microscopy. On the other hand, to elucidate the transcriptomics’ data, genes that were upregulated were singled out and validated using qpcr. The bulges apical tips were found to have shorter transit amplification (ta), more of coilin-positive (spermatocyte) cells’ number, and fewer elongating spermatids. Upregulated immune genes were validated as per suggested by the transcriptomics. The research models proposed to discuss the bulged apical tips are early differentiations, cell competition, rogue asymmetrical cell division, apoptosis aversion, and meiosis entry defects.